2013
DOI: 10.3390/molecules18089477
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Cytotoxicity Evaluation of Essential Oil from Leaves of Casearia Sylvestris, Its Main Compound α-Zingiberene and Derivatives

Abstract: Casearia sylvestris (Salicaceae), popularly known as "guaçatonga", is a plant widely used in folk medicine to treat various diseases, including cancer. The present work deals with the chemical composition as well as the cytotoxic evaluation of its essential oil, its main constituent and derivatives. Thus, the crude essential oil from leaves of C. sylvestris was obtained using a Clevenger type apparatus and analyzed by GC/MS. This analysis afforded the identification of 23 substances, 13 of which corresponded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 29 publications
(32 reference statements)
2
38
0
2
Order By: Relevance
“…Our findings were in line with previous reports. Similar to our findings, it was reported that the purified a-ZBN from the essential oil from leaves of Casearia sylvestris showed a cytotoxic activity against HeLa, U-87, Siha and HL60 cell lines (Bou et al 2013). Our results are also in agreement with previous studies which have reported that parthenolide demonstrated strong cytotoxicity towards human lung carcinoma (A549), human medulloblastoma (TE671), human colon adenocarcinoma (HT-29) cells in the MTT in vitro assay (Parada-Turska et al 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings were in line with previous reports. Similar to our findings, it was reported that the purified a-ZBN from the essential oil from leaves of Casearia sylvestris showed a cytotoxic activity against HeLa, U-87, Siha and HL60 cell lines (Bou et al 2013). Our results are also in agreement with previous studies which have reported that parthenolide demonstrated strong cytotoxicity towards human lung carcinoma (A549), human medulloblastoma (TE671), human colon adenocarcinoma (HT-29) cells in the MTT in vitro assay (Parada-Turska et al 2007).…”
Section: Discussionsupporting
confidence: 92%
“…ZBN has been used in the odors and cosmetics industry for a long time (Denyer et al 1994). Furthermore, previous reports indicated that ZBN has antifertility, antiviral, antiulcer and anticancer effects (Denyer et al 1994;Millar 1998;Bou et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There is an exciting piece of evidence suggesting that partially hydrogenated α-zingiberene isolated from essential oil from Casearia sylvestris was effective against B16F10-Nex2 cell line. However, surprisingly, fully hydrogenated derivative was effective against MCF-7 and B16F10-Nex2 (Bou et al, 2013).…”
Section: In-vitro Analysis Of Different Essential Oilsmentioning
confidence: 89%
“…The Casearia sylvestris specie was recently related to the family of Salicaceae (Ferreira et al, 2011) and contains phytochemicals from different classes of medicinal interest such as sesqui- (Bou et al, 2013) and diterpenes (Meesakul et al, 2016).…”
Section: Introductionmentioning
confidence: 99%